Similarities and Differences between Quantifier Raising and Wh Movement Out of Adjuncts. (17th October 2019) - Tanaka, Misako
Abstract: This article reports a set of experimental studies that support the following set of conclusions: (i) quantifier raising is sensitive to adjunct islands, (ii) wh movement is sensitive to adjunct islands, but (iii) quantifier raising and wh movement are not sensitive to adjunct islands in the same way. The experiments examined quantifier raising and wh ‐argument extraction from three types of nontensed adjuncts: bare participial gerunds, after prepositional gerunds, and during PPs. The results provide an interesting puzzle. On the one hand, quantifier raising and wh movement shared a weak sensitivity to adjunct islands. On the other hand, the two operations behaved differently when it came to extraction from bare participial gerunds. I argue that this asymmetry results from the different interface constraints that quantifier raising and wh movement are subject to: Scope Economy and the Single‐Event‐Grouping Condition, respectively.